Roman Pollak – badacz Seicenta na drogach nauki polskiej i europejskiej - Nowicka-Jeżowa, Alina (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article presents Roman Pollak’s scientific goals and methods from the point of view of their relationship with Polish science involved in the protection and promotion of the values considered to be national legacy and in the context of their dialogue with contemporary scientific trends. It also reconstructs the design of studies of past Polish literature and culture that the Poznan-based professor created and consistently followed – one based on philology, interdisciplinarity and comparative literature. This is the context for the presentation of Roman Pollak’s research into Polish 17th-century literature as it followed a path from discoveries in textology and editing to numerous attempts at synthesis. The synthetic outlines created in the pre-war period were inspired by contemporary European humanities, Italian in particular, and highlighted the aesthetic qualities of a literary work. After World War II, they became more sociological in nature and turned towards Polish literature. In place of categories like Seicentism and the Baroque, they introduced terms such as “post-Renaissance literature” and passed judgement on Sarmatism as a period of degeneration and decline of culture.